Superior operational stability of immobilized l-asparaginase over surface-modified carbon nanotubes - Almeida, Mafalda R.; Cristóvão, Raquel O.; Barros, Maria A.; Nunes, João C. F.; Boaventura, Rui A. R.; Loureiro, José M.; Faria, Joaquim L.; Neves, Márcia C.; Freire, Mara G.; Santos-Ebinuma, Valéria C. [UNESP]; Tavares, Ana P. M.; Silva, Cláudia G. (Springer Nature, 2021)
l-asparaginase (ASNase, EC 3.5.1.1) is an enzyme that catalyzes the l-asparagine hydrolysis into l-aspartic acid and ammonia, being mainly applied in pharmaceutical and food industries. However, some disadvantages are associated with its free form, such as the ASNase short half-life, which may be overcome by enzyme immobilization. In this work, the immobilization of ASNase by adsorption over pristine and modified multi-walled carbon nanotubes (MWCNTs) was investigated, the latter corresponding to functionalized MWCNTs through a hydrothermal oxidation treatment. Different operating conditions, including pH, contact time and ASNase/MWCNT mass ratio, as well as the operational stability of the immobilized ASNase, were evaluated. For comparison purposes, data regarding the ASNase immobilization with pristine MWCNT was detailed. The characterization of the ASNase-MWCNT bioconjugate was addressed using different techniques, namely Transmission Electron Microscopy (TEM), Thermogravimetric Analysis (TGA) and Raman spectroscopy. Functionalized MWCNTs showed promising results, with an immobilization yield and a relative recovered activity of commercial ASNase above 95% under the optimized adsorption conditions (pH 8, 60 min of contact and 1.5 × 10–3 g mL−1 of ASNase). The ASNase-MWCNT bioconjugate also showed improved enzyme operational stability (6 consecutive reaction cycles without activity loss), paving the way for its use in industrial processes.